EXPLORING THE POTENTIALS OF UNDERUTILIZED AFRICAN NUTS (BLACK WALNUTS AND ALMONDS) FOR NUTRITION AND DISEASES - Olaoye, Francis Sunday; Ezeoguine, Juliana; Uku, Florence (American Journal of Food Sciences and Nutrition, 2021)
Purpose: This study explores the potential of underutilized African nuts (Black walnuts and Almond) in nutrition and curing dietary diseases. The study attempts to find out the extent of consumption of Black walnut and Almonds among Staff and students of selected tertiary institutions in Nigeria and find out whether people not consuming these nuts (Walnuts and Almonds) have specific reasons for avoiding them. Methodology: The study adopted survey research design to generate data for the study. The population of the study comprised of staff and students across three main federal institutions in South-west region. The sample comprised of 300 respondents selected through a simple random sampling technique. The study also partly adopts interview to get the opinion of 30 randomly selected Traditional Herbal Practitioners in the study areas. Structured questionnaire designed based on the objectives of the study was used in data collection. Findings: Data generated showed that majority of the respondents have little or no knowledge about the culinary, medicinal and therapeutic benefits of these nuts let alone utilize them in their diets. The study also showed that majority of the respondents rejected these nuts because of negative allergic reactions (i.e. Acne, body itching, stomach cramp, diarrhea/vomiting and bitter after taste) experienced after consuming them. The report of some of the Traditional Herbal Practitioners interviewed corroborated the fact that Almonds and black walnuts have potentials for curing many dietary diseases. Conclusion: Based on these findings, the researchers conclude that Almonds and walnuts should form active parts of family's diet and that health officials and nutritionist should collaborate in organizing seminars and workshops on the need to live healthy life and fight against commons preventable diseases through consumption of nuts (walnuts and almonds)